A Legal Transplantation by The Rule of Law, Comparative Study, Legal Culture and History - Boy Nurdin (Jurnal Ilmiah Kebijakan Hukum, 2024)
Legal transplantation introduces foreign laws or institutions into a legal system without considering the existing legal culture, a process that poses significant challenges. When borrowing occurs through complete assimilation, these challenges are particularly evident. This research aims to develop a theoretical framework for legal transplantation through the lens of path dependence, a framework that can address the challenges that arise from the historical development of legal systems. To accomplish this aim, a systematic literature review (SLR) was conducted. This entailed the selection and analysis of articles published between 2019 and 2024 that focused on specific subjects, including legal transplantation practices, legal path dependence practices, and law creation from legal history. The articles were obtained from the Scopus database, which is a widely recognized global journal database. The results indicate that the development of a theoretical framework for legal transplantation by path dependence encompasses legal discussions and the rule of law by the judiciary in the home country, considering the challenges posed by recent cultural structures. The article elucidates the pivotal role of path dependence in legal system development through legal transplantation, while also underscoring its limitations and its manifestation in different countries.